Free Educational Environment as the Basis of Human Capital and Relationships between Social Sectors - Avetisyan, Parkev Sergeevich; Gevorgyan, Naira Miranovna (Economy of Regions, 2020)
The article examines the conditions for establishing a free educational environment that acts as a basis for the development of intellectual human capital and links main social sectors. This topic is relevant for both the Republic of Armenia, Russia and other countries of the former Soviet Union. There is a certain imbalance, as modern higher education is inconsistent with the challenges caused by the spread of new digital technologies in the global educational environment. Such wide dissemination enhances the internationalization of education, increases the competitiveness of the higher education system, and affects the development of human capital. Intellectual human capital is at the core of the social organism, while education is the basis for its development. In this regard, we identified the important tasks facing the higher education system of the Republic of Armenia. Using the analysis of the global trends, academic literature and expert opinions, we described how to transform the education system into a single free space, which enables the development of a country’s intellectual human capital in the context of digitalization. In this case, internationalization and digitalization (as well as their interconnection) act as both tools and conditions for the development of the modern education system. We created a model demonstrating the links between social sectors based on the development of the educational environment with intellectual human capital at its core. In conclusion, we suggest how to solve the problems facing the education system. Educational specialists participating in digitalization can use the research results in order to improve the educational processes and policies of the Republic of Armenia.